EFFECT OF PHARMACEUTICAL CARE ON LEVEL OF SATISFACTION AND KNOWLEDGE IN HYPERTENSIVE PATIENTS AT THE RSUD DR. SOEKARDJO CITY OF TASIKMALAYA - Hernaeni Hernaeni; Ilham Alifiar; Nur Rahayuningsih (Jurnal Farmasi Sains dan Praktis, 2020)
High blood pressure is described as an increase in blood vessel pressure when the heart pumps against the walls of the blood vessels. Satisfaction is the feeling of satisfaction received by the patient/person experiencing the treatment. This study aims to measure the level of adherence, satisfaction, and knowledge of drug use before and after counselling. This research was conducted experimentally with primary data collection in the form of information from patients prospectively from February to April 2019. The instruments used were the compliance questionnaire (MMAS-8), satisfaction, and knowledge. Respondents involved in this study were 50 people. The testing group was divided into two, namely the group that was given treatment and the group that was not given treatment, where the treatment group was given counselling by the pharmacist. The results of statistical testing showed a value (p <0.05) on the level of compliance, satisfaction, and knowledge. The test results showed a significant value (P <0.05) between compliance with knowledge and satisfaction. Meanwhile, there is no significant result between satisfaction and knowledge. It can be concluded that there is a correlation between the level of knowledge with compliance, compliance with satisfaction and there are differences in the level of compliance, satisfaction, and knowledge before and after being given pharmaceutical/counselling care.